The Role of Scientific Approaches in Increasing Creativity and Innovation Through Discovery Learning in Science Learning in Elementary School - aulia zahwa adinda; dinda kusumawati subagio; khairani ulya; miftahul jannah (Journal of Pedagogical Content Knowledge, 2025)
This study aims to analyze the impact of the implementation of the scientific approach and the Discovery Learning model in learning Natural and Social Sciences (IPAS) at the elementary school level, with a focus on developing students' critical and creative thinking skills. This study was conducted using a literature review method, in which various sources of literature, such as scientific journals, textbooks, and relevant research articles were analyzed in depth. The results of the literature review indicate that the scientific approach, which involves the stages of observing, formulating questions, experiments, analysis, and conclusions, is effective in increasing student engagement in the learning process, and is able to develop critical thinking skills. Meanwhile, the Discovery Learning model that encourages students to find knowledge independently through exploration and direct experience, has been shown to increase students' creativity and their ability to solve problems innovatively. This literature review also revealed that both approaches provide a more meaningful and relevant learning experience, and support the development of 21st century skills, such as critical, creative, collaborative, and communicative thinking. Thus, the implementation of the scientific approach and Discovery Learning in elementary schools is recommended as an effective strategy in optimizing students' intellectual and creative potential.